1997
DOI: 10.1038/bjc.1997.339
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between folate-binding protein expression and cisplatin sensitivity in ovarian carcinoma cell lines

Abstract: Summary It has been suggested that sensitivity of ovarian carcinomas to cisplatin is in part related to an endogenous folate deficiency. In this work, we investigated whether overexpression of the folate-binding protein (FBP), a receptor involved in folate transport, might be associated with cisplatin sensitivity. The results obtained on a panel of ten ovarian carcinoma cell lines that overexpress different levels of the FBP showed a statistically significant relationship between FBP overexpression and cisplat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Experiments we previously performed in vitro on ovarian carcinoma cell lines did not address this issue, giving conflicting results (Ottone et al, 1997). Some hypotheses could be proposed: FBP, by increasing cellular uptake of folates, could render cells more prone to repair DNA damage caused by platinum.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Experiments we previously performed in vitro on ovarian carcinoma cell lines did not address this issue, giving conflicting results (Ottone et al, 1997). Some hypotheses could be proposed: FBP, by increasing cellular uptake of folates, could render cells more prone to repair DNA damage caused by platinum.…”
Section: Discussionmentioning
confidence: 89%
“…A significant relationship between FBP overexpression and cisplatinum responsivity was observed; however, the receptor did not appear to be directly responsible for drug sensitivity. It is noteworthy that we found that the human ovarian cancer cells SKOV-3 transfected with FBP required cisplatinum concentrations about 3-fold higher in culture medium than control cells for equitoxic effects (Ottone et al, 1997).…”
Section: Wiley-liss Incmentioning
confidence: 98%
“…Although weekly cisplatin at 40 mg/m 2 for six weeks is the standard of care for locally advanced cervical carcinoma in many cancer centers as ours, its optimal scheduling and dosing have yet to be established due to the frequent development of therapy resistance (Candelaria et al, 2006). Different mechanisms have been proposed to reduce cisplatin response, including altered drug accumulation, enhanced drug detoxification and DNA repair, or upregulation of specific biochemical pathways (Ottone et al, 1997;Siddik, 2003). Thus, the identification of molecular predictors of response urges (Siddik, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…FR expression, on normal epithelial cells such as in kidney proximal tubules, breast, and choroid plexus (32), is restricted to the apical (luminal) surface of polarized cells, on which it is not exposed to the bloodstream and not accessible to antibody (33). Moreover, expression of FR is associated with tumor progression in ovarian carcinoma (34); and, importantly, on the basis of published (35) and unpublished data, the expression of the FR is stable or even upmodulated during acquisition of drug resistance. In support of the mentioned preclinical and clinical data, the humanized anti-FR mAb farletuzumab is now in phase II and III clinical trials in combination with chemotherapy (36).…”
Section: Discussionmentioning
confidence: 99%